OBM Geriatrics 2021
DOI: 10.21926/obm.geriatr.2101159
|View full text |Cite
|
Sign up to set email alerts
|

Acute Care Decision-Making for Patients with Advanced Dementia: An Exploratory Study Using Cognitive Task Analysis

Abstract: Decision-making by medical and health care staff forms the core of professional practice. Thought processes, including non-clinical considerations, significantly impact how clinical decisions are made. Such considerations become more relevant when addressing end-of-life care decisions for patients with advanced dementia (PAD). Though palliative care is recommended for this population, its implementation tends to vary. Given the medical staff’s significant influence in guiding clinical decisions, we examined th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 47 publications
2
5
0
Order By: Relevance
“… Nabozny et al (2016) found that internists were more than twice as likely to base treatment decisions on quality of life than surgeons. This finding is reinforced by the findings from the qualitative part of this study ( Erel et al, 2021a ). The majority of medical ward staffs perceived quality of life and the palliative care approach as the most appropriate care, while the surgical ward staffs perceived aggressive care (surgical intervention) to be best.…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“… Nabozny et al (2016) found that internists were more than twice as likely to base treatment decisions on quality of life than surgeons. This finding is reinforced by the findings from the qualitative part of this study ( Erel et al, 2021a ). The majority of medical ward staffs perceived quality of life and the palliative care approach as the most appropriate care, while the surgical ward staffs perceived aggressive care (surgical intervention) to be best.…”
Section: Discussionsupporting
confidence: 77%
“…Many surgical cases may be perceived as potentially treatable and reversible with a better prognosis, such as the removal of a benign tumor. Two studies comparing medical to surgical staff found an association between medical education and goals of care ( Erel et al, 2021a ; Nabozny et al, 2016 ). Nabozny et al (2016) found that internists were more than twice as likely to base treatment decisions on quality of life than surgeons.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is a cross sectional survey, part of a mixed-methods (qualitative/quantitative) research study that evaluates preferences of physicians and nurses regarding treatment choices, including PC, for patients with AD under acute care settings. The qualitative part of the study included an interview assessing the thought processes involved in decision-making regarding a hypothetical case scenario of a patient with AD who presents with bowel obstruction related to a space-occupying lesion [ 18 ].…”
Section: Methodsmentioning
confidence: 99%
“…Health personnel who consider care options that do not follow this approach may receive negative responses from their peers, which can lead to suppressing their initial intentions [ 16 , 17 ]. Factors associated with this approach are related to legal concerns, hierarchical and organizational authority, and responses of patient’s relatives [ 12 , 13 , 18 ].…”
Section: Introductionmentioning
confidence: 99%